Optimization of Feed Formulation, Feeding Rate, and Plant-Based Supplements for Efficient Rearing of the Superworm Zophobas morio (Fabricius) Under Tropical Conditions - J. Pumnuan; Noratat Prachom; Somsak Kramchote (Insects, 2026)
production under tropical conditions, contributing to circular bioeconomy strategies and supporting insect-protein innovation.
Keywords: Insect Utilization and Effects; Silkworms and Sericulture Research; Insect Pest Control Strategies